Pembentukan Kader GPS2 (Gerakan Perempuan Sehat dengan SADARI) Sebagai Upaya Peningkatan Cakupan Deteksi Dini Kanker Payudara - Nadhiroh, Aim Matun; Irma Maya Puspita; Asta Adyani; Awwalul Wiladatil Qodliyah; Annisa’ Wigati Rozifa (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this community service is to improve the knowledge and attitudes of adolescents and women of childbearing age about breast cancer, and to increase the motivation of women of childbearing age to perform early detection of breast cancer with BSE. The method of solving the problem is by socializing about breast cancer and early detection of cervical cancer in a programmed manner; health education through counseling about breast cancer and early detection of breast cancer with BSE. This community service includes an initial survey, preparation, implementation (socialization and counseling about breast cancer and the importance of early detection of breast cancer with BSE, Socialization about BSE and how to do it, and Early detection of breast cancer with BSE examination, and evaluation of activities. The results of this community service activity are an increase in the knowledge and attitudes of adolescents and women of childbearing age about breast cancer, as well as an increase in the motivation of adolescents and women of childbearing age which is indicated by performing early detection of breast cancer with BSE